A worldwide sectorial analysis of sustainability reporting and its impact on firm performance. (2nd January 2022) - Al Hawaj, Abdulla Yusuf; Buallay, Amina Mohamed
ABSTRACT: This study investigates the worldwide impact of sustainability reporting on firms' performance across seven different sectors. Using data culled from 3, 000 firms in 80 different countries for ten years from 2008 to 2017 (cumulatively 23, 738 observations). The findings elicited from the empirical results demonstrate that there are differences in the impact of sustainability reporting (ESG) on firm's operational performance (ROA), financial performance (ROE) and market performance (TQ) between the seven sectors. Inasmuch as it contributes to the literature of sustainability accounting by a systematic depiction of cross-sectorial ESG reporting, this study establishes a benchmark to guide to firms wishing to adopt sustainability reporting. Moreover, in including macroeconomic variables, the study provides a fresh perspective to the literature of the on the economic implications of sustainability disclosure.